The relation between cigarette smoking and risk of acute myeloid leukemia: An updated meta‐analysis of epidemiological studies. Issue 8 (8th May 2014) - Fircanis, Sophia; Merriam, Priscilla; Khan, Naushaba; Castillo, Jorge J.
<x xml:space="preserve">Abstract</x> Smoking has been postulated as an environmental risk factor for acute myeloid leukemia (AML). The primary objective of this meta‐analysis of observational studies was to evaluate the epidemiologic relationship between smoking and the risk of development of AML. Twenty‐three studies published between January 1993 and December 2013 were included in our analysis, and accounted for 7, 746 cases of AML. The outcome of interest was the relative risk (RR) with 95% confidence interval (CI) of developing AML in adult cigarette smokers in comparison with non‐smokers, and was estimated using the random‐effects model. Our results showed that current and ever smokers have 40% (RR 1.40, 95% CI 1.22–1.60; P < 0.001) and 25% (RR 1.25, 95% CI 1.15–1.36; P < 0.001) increased risk of developing AML when compared with non‐smokers. The increased RR of AML was increased regardless of sex, study design, geographical region, and quality of the studies. Intensity of smoking of <10, 10–20, 20–30, and >30 cigarettes per day was associated with RRs of AML of 1.27, 1.36, 1.55, and 1.77, respectively (P < 0.001 for trend). Duration of smoking of <20 and >20 years was associated with RRs of 1.07 and 1.44, respectively (P < 0.001 for trend). Cumulative smoking of <10, 10–20, 20–30, and >30 pack‐years was associated with RRs of 1.13, 1.23, 1.39, and 1.71, respectively (P < 0.001 for trend). Overall, cigarette smoking proves to be a significant risk factor for the development of AML in adults. Am. J. Hematol. 89:E125–E132, 2014. © 2014 Wiley Periodicals, Inc.